Pemberdayaan Masyarakat Melalui Bumdes Di Desa Sirapan Kecamatan Madiun, Kabupaten Madiun - Anik Tri Haryani (JURNAL DAYA-MAS, 2019)
KKN is a form of education by providing learning experiences to students to live in the midst of society, structured through several stages including preparation, briefing, observation until the evaluation stage. Preparation is the initial stage before KKN is implemented, the preparation is done so that the activities can be done in a structured and directed according to plan. Village Sirapan, Madiun District, Madiun Regency is one of the many villages that became the goal of KKN Universitas Merdeka Madiun. Implementation of KKN is done through socialization or counseling, training and mentoring. Socialization is done by giving counseling about BUMDes to empower the community also given the training of processed food made from tempe as well as the utilization of vacant land for vegetable and toga crops as well as training the making of MOL (Micro Organism Local) as organic fertilizer.